Novel Co-Precipitation method for synthesis of Nanostructured Nickel Oxide in accordance to PH: Structural and Optical Properties as an Active optical filter - Abdul-Ameer, Zehraa N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Low cost Co-Precipitation  method was used for Preparation of novel nickel oxide (NiO) nano particle thin films with Simple, with two different PH values 6, 12 and its effect on structural and optical properties as an active optical filter. Experimental results of structural properties X-ray diffraction (XRD) showed that both Nickel oxide nanoparticles with (PH=6 and 12) have polycrystalline structure smaller average particle size about 8.5 nm for PH=6 in comparison with PH=12. Morphological studies using Scanning electron microscopy (SEM) and  atomic force microscope (AFM)  show uniform nano rod distribution for PH=6 with smaller average diameter, average roughness as compared with NiO with PH=12 that showed larger diameter ,grain size , spherical shape with scope of excellent sensing applications due to high roughness .Optical properties results  Show blue shift for PH=6 as compared with PH=12m leading to potential of optoelectronic applications and as active optical